PEMAKAIAN GOOGLE FORM SEBAGAI MEDIA PENUNJANG EVALUASI PEMBELAJARAN BERBASIS ONLINE - Miftahuddin; Farida, Titin (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
The research aim on this study to describe the use of Google Forms as a tool for evaluating learning, advances in information technology make educators required to integrate it within the scope of learning and conventional media are starting to be abandoned. This research uses descriptive qualitative method. The results of this study indicate that the use of the Google form in evaluating online learning requires readiness in terms of facilities and infrastructure, human resources, and synergy between educational institutions and student guardians. The benefits provided are in the form of flexibility in carrying out evaluations, efficiency in carrying out evaluations, and providing a stimulus for student interest in carrying out evaluations. While the obstacles that are often encountered are the uneven ability of teachers and students, signal quality that is less than optimal, and the tendency of parents not to be able to accompany their children during the learning evaluation process.